Understanding the role of policy in enhancing agrifood value chain competitiveness: A systematic literature review - Saroj Amgai; Adam M. Komarek; Rajendra P. Adhikari (Journal of Agriculture and Food Research, 2025)
The value chain, as an inter-firm concept, has been established as a distinctive source of sustainable competitive advantage. Similarly, sound institutions and policy responses in firms or businesses are crucial to improving value chain competitiveness. Previous studies on competitiveness have examined factors, drivers, and outcomes in isolation, lacking comprehensive evidence on their interrelations and the role of policy in enhancing overall chain competitiveness. This study adopted a deductive thematic approach to systematically review the literature on agrifood value chains and policy across five theoretical views of competitive advantage: resource-based, relational, innovation-based, dynamic capability, and institution-based. Competitiveness factors identified from 171 studies from the systematic literature review were mapped to the five themes using a systems thinking approach to illustrate their cause-and-effect relationships in a causal loop diagram. The results revealed that productivity, chain networking, product diversity, market access, and extension services are primary drivers that influence the interrelationships among competitiveness factors and overall chain competitiveness across five themes. In addition, policies, whether short-term or long-term, emerge as an overarching domain that drives chain-wide competitiveness. The findings also indicate that short-term policy initiatives aimed at facilitating participation in global value chains through improved market access can enhance chain competitiveness. However, sustaining long-term competitiveness requires policy measures to support chain actors, particularly by improving access to finance and essential input resources.